Development and Validation of a Fast Stability-Indicating Ion-Paired Reversed-Phase HPLC Method for the Assay of Thiabendazole and Estimation of Its Related Compounds. (22nd November 2019) - Zhang, Peng; Tian, Jingzhi; Rustum, Abu
Abstract: Thiabendazole is a benzimidazole-based anthelmintic active pharmaceutical ingredient for the treatment of intestinal pinworm and Strongyloides infections. Thiabendazole is also used as a fungicide to control fungal diseases in fruits and vegetables. In this paper, we report, for the first time, the development and validation of a novel stability-indicating reversed-phase ion-paired HPLC method for the assay of thiabendazole and estimation of its related compounds. Chromatographic separation was achieved by using an isocraticelution at a flow rate of 1.5 mL/min using an ACE 5 C18 (4.6 × 50 mm, 5 μm particle size) columnmaintained at 35°C and with UV detection at 300 nm. The mobile phase consisted of 25% acetonitrile and75% 10 mM 1-octanesulfonic acid sodium salt aqueous solution containing 0.1% methanesulfonic acid. The total run time was only 4 min. The new method was successfully validated according to the International Conference on Harmonization guidelines. The stability-indicating capability of the method was demonstrated through adequate separation of all potential related compounds (from thiabendazole and from each other) present in aged and stressed degraded samples. The ion-paired HPLC method described in this paper is ideal for QC laboratories to conduct routine testing.